Antibiograms from community-acquired uropathogens in Gulu, northern Uganda - a cross-sectional study - Odongo, Charles O.; Anywar, Denis A.; Luryamamoi, Kenneth; Odongo, Pancras (BMC infectious diseases, 2013)
Urinary tract infections (UTI) are common in clinical practice and empirical treatment is largely employed due to predictability of pathogens. However, variations in antibiotic sensitivity patterns do occur, and documentation is needed to inform local empirical therapy. The current edition of the Uganda Clinical Guidelines recommends amoxicillin or cotrimoxazole as choice drugs for empirical treatment of community-acquired UTI. From our clinical observations, we suspected that this recommendation was not effective in our setting. In order to examine validity, we sought to identify bacteria from community-acquired infections and determine their susceptibility against these antibiotics plus a range of potentially useful alternatives for treatment of UTI. Methods: A cross-sectional study of mid-stream urine collected from 339 symptomatic patients over a three-month period at Gulu regional referral hospital. Qualitative culture and identification of bacteria and antibiotic sensitivity testing using the modified Kirby-Bauer disk diffusion method was done. Participants’ demographic and clinical characteristics were collected using a standard form. Results were analyzed by simple proportions among related variables and confidence intervals computed using binomial exact distribution. Results: Eighty two cultures were positive for UTI. Staphylococcus spp (46.3%) and Escherichia coli (39%) were the most common pathogens. There was high resistance to cotrimoxazole (73.2%), nalidixic acid (52.4%) and amoxicillin (51.2%). The most favorable antibiograms were obtained with gentamicin, amoxicillin-clavulanate and levofloxacin where 85.4%, 72.0%, 67.1% of isolates respectively, were either sensitive or intermediate. Only 51% of isolates were sensitive to ciprofloxacin.
Keywords: Antibiograms; Antibiotic resistance; Uropathogens Empirical treatment; Uganda